THE ROLE OF GOVERNANCE, AND SUSTAINABLE DEVELOPMENT IN SOUTH SUDAN - Riak , Dr Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
The Governance as the exercise of political, economic and administrative authority in the management of a country’s affairs at all levels (UNDP, 2006). For UNDP governance “comprises the complex mechanisms, processes and institutions through which citizens and groups articulate their interests, mediate their differences and exercise their legal rights and obligations. Union Development Agency, defines governance as the ability and capacity of a government to fulfill its mission (Mbaku& Smith, 2012). According to Brinkerhoff, the design and implementation of governance reforms in post-conflict states target three areas; reconstituting legitimacy, re-establishing security and rebuilding effectiveness (Ranz, 2009). According to Brinkerhoff & Derick, (2008) a government is essential to providing security, justice, economic, and social functions and to channeling the will, energies, and resources of both the indigenous population and the international community (Ranz, 2009). Good governance is related to a set of values such as participation, accountability, responsiveness and rule of law by (World development report, 2011).